Silver Nanoparticles‐Silsesquioxane Nanomaterial Applied to the Determination of 4‐Nitrophenol as a Biomarker. Issue 12 (25th July 2019) - Crocomo, Paola Zimmermann; Winiarski, João Paulo; de Barros, Marília Reginato; Latocheski, Eloah; Nagurniak, Glaucio Régis; Parreira, Renato Luis Tame; Siebert, Diogo Alexandre; Micke, Gustavo Amadeu; Magosso, Hérica Aparecida; Jost, Cristiane Luisa
Abstract: A novel silsesquioxane material was synthetized and used as a stabilizing agent for silver nanoparticles. This hybrid material was characterized by FTIR, 29 Si CP‐MAS NMR, 13 C DEPT 135° NMR and TGA techniques and the silver nanoparticles were characterized from DLS, UV‐Vis spectroscopy, zeta‐potential, TEM and SAXS results. The silver nanoparticles obtained were spherical in shape with a diameter of 3.74 nm. The nanomaterial was successfully applied in the modification of a glassy carbon electrode and a pronounced current response was obtained in the determination of the biomarker 4‐nitrophenol. Quantum chemical calculations, using density functional theory, were also performed in order to evaluate the redox properties of the analyte. Two different linear ranges were obtained applying optimal square wave voltammetry conditions. The reduction peak currents obtained were linear for 4‐NP concentrations in the ranges of 0.29 to 1.50 μmol L −1 (Ed =−0.6 V and td =20 s) and 2.75 to 31.5 μmol L −1, with a theoretical (signal to noise=3) limit of detection of 0.05 μmol L −1 (td =20 s). The proposed method was successfully applied to the determination of 4‐NP in synthetic serum samples at different levels of 4‐NP with a recovery range of 94–101 %. Validation was performed using a comparative method through the capillary electrophoresis (CE) technique. Abstract :